2014
DOI: 10.1093/nar/gku1381
|View full text |Cite
|
Sign up to set email alerts
|

A robust assay to measure DNA topology-dependent protein binding affinity

Abstract: DNA structure and topology pervasively influence aspects of DNA metabolism including replication, transcription and segregation. However, the effects of DNA topology on DNA-protein interactions have not been systematically explored due to limitations of standard affinity assays. We developed a method to measure protein binding affinity dependence on the topology (topological linking number) of supercoiled DNA. A defined range of DNA topoisomers at equilibrium with a DNA binding protein is separated into free a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Topo IB inhibitor-mediated DNA cleavage complex formation is enhanced by supercoiling of the DNA substrate (Seol et al 2015), although the relative enhancement is modulated by the chirality of supercoiling, the specific type of inhibitor, and the inherent chiral-dependence of cleavage (Gentry et al 2011;McClendon and Osheroff 2006;Seol et al 2015). This enhancement may arise from the higher affinity of Topo IB for supercoiled DNA (Madden et al 1995), possibly due to preferential binding at DNA crossovers (Patel et al 2010;Zechiedrich and Osheroff 1990); however, recent measurements performed at low Topo IB concentrations suggest there is little difference in affinity between relaxed and supercoiled DNA (Litwin et al 2015). Alternatively, enhanced Increased torsion also hinders and can reverse DNAwrapping interactions of nucleosomes.…”
Section: Dna Twist (Torsion)-dependent Protein Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Topo IB inhibitor-mediated DNA cleavage complex formation is enhanced by supercoiling of the DNA substrate (Seol et al 2015), although the relative enhancement is modulated by the chirality of supercoiling, the specific type of inhibitor, and the inherent chiral-dependence of cleavage (Gentry et al 2011;McClendon and Osheroff 2006;Seol et al 2015). This enhancement may arise from the higher affinity of Topo IB for supercoiled DNA (Madden et al 1995), possibly due to preferential binding at DNA crossovers (Patel et al 2010;Zechiedrich and Osheroff 1990); however, recent measurements performed at low Topo IB concentrations suggest there is little difference in affinity between relaxed and supercoiled DNA (Litwin et al 2015). Alternatively, enhanced Increased torsion also hinders and can reverse DNAwrapping interactions of nucleosomes.…”
Section: Dna Twist (Torsion)-dependent Protein Activitymentioning
confidence: 99%
“…To date, however, the proposed models cannot fully explain the below-equilibrium simplification phenomenon, indicating that the models may only partially reflect the mechanistic basis of this intriguing effect (Hardin et al 2011;Liu et al 2010;Martínez-García et al 2014;Seol et al 2013b;Thomson et al 2014;Yan et al 1999). Recently, it was demonstrated that the binding affinity of Topo IV is linearly related to the linking number for negatively supercoiled plasmid DNA (Litwin et al 2015), which is consistent with previous observations of Topo IIA binding to DNA crossovers (Zechiedrich and Osheroff 1990). Although the exact mechanism for linking number-dependent binding affinity is uncertain, it highlights how DNA supercoiling and protein activity are dynamically coupled to each other.…”
Section: Dna Twist (Torsion)-dependent Protein Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Topo IB-inhibitor mediated DNA cleavage complex formation is enhanced by supercoiling of the DNA substrate (Seol et al 2015), though the relative enhancement is modulated by the chirality of supercoiling, the specific type of inhibitor, and the inherent chiral-dependence of cleavage (Gentry et al 2011; McClendon and Osheroff 2006; Seol et al 2015). This enhancement may arise from the higher affinity of Top1 for supercoiled DNA (Madden et al 1995) possibly due to preferential binding at DNA crossovers (Patel et al 2010; Zechiedrich and Osheroff 1990), however, recent measurements performed at low Top1 concentrations suggest there is little difference in affinity between relaxed and supercoiled DNA (Litwin et al 2015). Alternatively, enhanced inhibitor mediated cleavage with supercoiled DNA may reflect the torque-dependent increase in the occupancy of a cleaved, but not rotating, DNA-protein conformation that promotes inhibitor binding (Seol et al 2012).…”
Section: Dna Twist (Torsion) Dependent Protein Activitymentioning
confidence: 99%
“…Most common ensemble techniques to investigate topology modifying enzymes such as DNA topoisomerases are based on gel electrophoresis approaches that can separate DNA topoisomers with single linking number resolution, in addition to resolving different knotted DNA species (Keller 1975). Topology dependent protein binding can be measured with several approaches including the electrophoretic mobility shift assay (EMSA) (Osheroff 1986; Palecek et al 2001), atomic force microscopy (Alonso-Sarduy et al 2011; López et al 2012; Vanderlinden et al 2014), and an equilibrium topology-dependent binding assay (Litwin et al 2015). Single-molecule techniques that can control as well as measure the topology of individual DNA molecules extend our capacity to directly observe how DNA topology modulates the activities of proteins and the dynamic nature of the interplay between protein activity and topology [reviewed in (Charvin et al 2004; Charvin et al 2005a; Forth et al 2013; Koster et al 2010; Lipfert et al 2015; Ma and Wang 2014; Neuman 2010; Strick et al 2000)].…”
Section: Introductionmentioning
confidence: 99%